Suggestions and Propositions for Successful Aging - María Guillermina Yanes García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
This article presents a manual that addresses old age focusing in propositions mainly related to aspects that contribute to develop traits reinforcing and enriching spiritual and emotional life of individuals. Such aspects include cohabitation and communication skills, improved self-perception of physical characteristics, self-esteem and motivation, among other issues that are actually involved in the balance between health and sickness. Themes that have been identified by elderlies as part of their health problems are also included. In addition, the actions and solutions proposed for these problems are taken into account. The aim is to open up new horizons of growth and development in order to improve elderlies' capacities to address the acceptation and adaptation issues they need to go through.